The Problem of implementing employees’ Empowerment in the Economic enterprises - BOUTAA, SALIMA; BOUKHEMKHEM, ABDELFATTEH (Milev Journal of Research and Studies, 2015)
The problems and obstacles that reduce the effectiveness and efficiency of enterprises are continually growing, especially in the light of the successive developments and rapid changes experienced by the word today. This requires the search for new managerial approaches that would help the enterprises to face these problems. Empowering employees is considered as a contemporary managerial approach that is applied in the field of human resources management. This concept came to confirm the necessity of finding an adequate and safe work environment that includes supporting the employees, integrating them to participate in the process of taking decisions and solving problems. The problematic of this research is about empowering employees, according to the awareness of officials and control agents, is applied at The Algerian enterprise of electricity Sonelgaz- Jijel. And the study included the confirm of major null hypotheses cause the statistical testes are not significant.